Tingkat Pendidikan Dan Status Sosial Ekonomi Pada Ibu Yang Memanfaatkan Pelayanan Penanganan Diare Pada Balita di Wilayah Kerja Puskesmas Jenu - Nirwana Prapti, Tri Nur Wahyu; Wahyurianto, Yasin; P, Teresia Retna (Jurnal Ilmiah Wahana Pendidikan, 2024)
Diarrhea is a health problem in Indonesia both in urban and rural. The achievement of children with toddler diarrhea decreases due to Covid-19. The purpose of the study was to know the description of the level of education and socio-economic status of mothers who took advantage of diarrhea handling services for toddlers in the work area of the Jenu Health Center. The research design is descriptive. The population used was all mothers who had toddlers with a history of diarrhea in the working area of the Jenu Health Center, totaling 335 people. The sample of this study was 183 mothers who had toddlers with a history of diarrhea in the working area of the Jenu Health Center. Using Simple Random Sampling. Retrieval of data with questionnaires and descriptive analysis using frequency tables. The results showed that most of the mothers who used diarrhea handling services in the Jenu Health Center Work Area were aged between 25-34 years (55%), almost all of whom had ≤ 2 children (87%), almost half of whom had a low level of education (45%), most of them have middle socioeconomic status (69%). The mother's education level is low but most of the mothers are of productive age. Education is directly proportional to knowledge. Increasing age affects the increase in knowledge acquired. Knowledge can be obtained from information from health workers, electronic media, and print media. Middle socioeconomic status with several children ≤ 2 means that family welfare is guaranteed, having many children will have an impact on high expenses for necessities. Children also have better access to health services and care.